ABCG Transporters Are Required for Suberin and Pollen Wall Extracellular Barriers in Arabidopsis . Issue 9 (12th September 2014) - Yadav, Vandana; Molina, Isabel; Ranathunge, Kosala; Castillo, Indira Queralta; Rothstein, Steven J.; Reed, Jason W.
Abstract : Plants make tough barriers outside their cells in precise anatomical locations to control water and solute movement through their tissues. This work demonstrates that a family of transport proteins is required in Arabidopsis to form such barriers in roots and in seed coats and to make a functional pollen wall. Abstract: Effective regulation of water balance in plants requires localized extracellular barriers that control water and solute movement. We describe a clade of five Arabidopsis thaliana ABCG half-transporters that are required for synthesis of an effective suberin barrier in roots and seed coats (ABCG2, ABCG6, and ABCG20) and for synthesis of an intact pollen wall (ABCG1 and ABCG16). Seed coats of abcg2 abcg6 abcg20 triple mutant plants had increased permeability to tetrazolium red and decreased suberin content. The root system of triple mutant plants was more permeable to water and salts in a zone complementary to that affected by the Casparian strip. Suberin of mutant roots and seed coats had distorted lamellar structure and reduced proportions of aliphatic components. Root wax from the mutant was deficient in alkylhydroxycinnamate esters. These mutant plants also had few lateral roots and precocious secondary growth in primary roots. abcg1 abcg16 double mutants defective in the other two members of the clade had pollen with defects in the nexine layer of the tapetum-derived exine pollen wall and in the pollen-derived intine layer. Mutant pollen collapsed at the time of anther desiccation. These mutants reveal transport requirements for barrier synthesis as well as physiological and developmental consequences of barrier deficiency.